2018
DOI: 10.1016/j.cplett.2018.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Shape controlled gold nanostructures on de-alloyed nanoporous gold with excellent SERS performance

Abstract: In this study, nanoporous gold (NPG) has been prepared by chemical de-alloying the Au based metallic glass precursor, Au 20 Cu 48 Ag 7 Pd 5 Si 20 (at.%), which was rapidly solidified from the melt in the form of ribbons. On the nanoporous gold, shape controlled gold nanostructures were electrodeposited by adjusting the applied potentials and deposition times. Using Rhodamine 6G (R6G) as probe molecule, the surface enhanced Raman scattering (SERS) activities with different Au nanostructures on nanoporous gold w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Amorphous ribbons about 20 mm thick and 2 mm wide were obtained by melt spinning. The NP Au samples were prepared by dealloying amorphous ribbons in free corrosion conditions at 70 °C in an aqueous solution of 10 M HNO 3 and 0.5 M HF for 4 h [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Amorphous ribbons about 20 mm thick and 2 mm wide were obtained by melt spinning. The NP Au samples were prepared by dealloying amorphous ribbons in free corrosion conditions at 70 °C in an aqueous solution of 10 M HNO 3 and 0.5 M HF for 4 h [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is a corrosive solution such as an acid in the case of chemical dealloying, the constant potential for electrochemical dealloying and the nature of liquid metal medium and temperature are the crucial deciding factors in the emerging field of liquid metal dealloying [11]. Extensive investigations have demonstrated that nanoporous metals with 3-D bicontinuous structures fabricated by the dealloying method, has many active sites for the excitation of localized surface plasmons and can, therefore, serve as a potential substrate for practical surface-enhanced Raman scattering (SERS) application [23]. Unlike single-sized porous materials, a hierarchical (bimodal) porous structure can impart novel properties to the material wherein large pores can favor increased mass transport and small pores can impart high specific surface area [24].…”
Section: Self-assemblymentioning
confidence: 99%
“…In particular, nanoporous metals prepared by dealloying techniques have been receiving research interest and exhibit promising results in several fields of application: actuators [ 1 ], storage and conversion of energy [ 2 ], electrodes for electrocatalysis [ 3 , 4 ], electrochemical biosensors [ 5 , 6 , 7 ], and surface-enhanced Raman scattering [ 8 , 9 ]. Scattering enhancement has been ascribed to their high surface area and their morphology constituted in ligaments, ranging from tens to hundreds of nanometers, and basically composed of the noblest elements of the original alloy.…”
Section: Introductionmentioning
confidence: 99%